Implementation of the Inlistile Application Information System in Library Services at SMP Negeri 9 Probolinggo City - Mubaroq, Husni; Septiandika, Verto; Rahman, Fathur (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This article aims to explain how the inlistile information system is implemented for students at SMP Negeri 9 Probolinggo City. This Inlistile application has been implemented by the SMP Negeri 9 Probolinggo City library to be used to improve service quality. Changes in data management are influenced by the implementation of the inlistile application information system. This study aims to determine the application of new innovations in the school library of SMPN9 Probolinggo City. This study uses a descriptive qualitative method with data collection techniques through in-depth interviews. The researcher conducted interviews with 5 library employees at SMPN9 Probolinggo City, 6 students who were members of the library. The application of application information systems in the SMPN9 Probolinggo City library includes: 1) increasing the convenience of professional services in a library and facilitating the service system; 2) provide friendly service attitudes and behaviors for students that aim to create an environmentally friendly environment; 3) increased student accessibility to get fast service; 4) provide services with an easy and reliable system. Encouraged by this application, students are expected to be able to make good use of this information technology system in order to realize a good service system in the school library.